FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DAN KINERJA KARYAWAN (Studi Kasus Pada Karyawan Universitas Banten Jaya Serang-Banten) - Urika Urika Urika (Jurnal Manajemen dan Bisnis, 2021)
This study aims to identif and explain:the influence of factors of satisfaction (compensation, Work environment and Job characteristics on job satisfaction, effect of job satisfaction n performance; the nfluence of factors of job satisfaction (compensation, work environment, job characteristicis for performance. This type of research used in this research is explanatory research with quantitative approach. The variable in this research is compensation, work environment and job characteristics as independent variables, satisfaction working as a variable mediator and employee performance as the dependent variable. this study uses data obtained from questionnaires by respondents. the data analysis method used is descriptive analysis and path analysis. the results of path analysis showed that: compensation, work environment and job characteristics influence no significant effect on job satisfaction; job satisfaction significant and positive impact on employee performance; compensation, work environment and job characteristics not significant effect on employee performance